Malignant hyperthermia and the dilemma of Dantrolene’s unavailability: a case report - Abdullah Mahmood; Muhammad Faizan Abbasi; Lubna Shafiq; Sumiya Khan; Muaaz Mahmood; Saqib Mehmood Khan (Journal of the Pakistan Medical Association, 2025)
Malignant Hyperthermia (MH) is a rare disorder which is triggered in genetically susceptible individuals when exposed to non-depolarising muscle relaxant (Succinylcholine) and inhalational anaesthetics (Isoflurane, Desflurane, Sevoflurance, Halothane, etc.). If not treated promptly, it carries a significantly high mortality rate. The only approved drug for the treatment of MH is Dantrolene, which is not available in Pakistan and its availability in other countries is also limited. We encountered a case of MH on January 3, 2024, in a five-year-old girl during her recovery from general anaesthesia after undergoing Tenotomy of Flexor Digitorum Superficialis (FDS) tendon for her Camptodactyly. Isoflurane was used for the maintenance of anaesthesia. The patient developed high grade fever and muscle rigidity in her limbs during recovery from anaesthesia. Supportive treatment was started promptly and the patient was immediately shifted to the ICU from the recovery room. Unfortunately, due to unavailability of Dantrolene the patient did not survive the event despite rigorous attempts at resuscitation. Keywords: Malignant Hyperthermia, Dantrolene, Camptodactyly.